2020
DOI: 10.3389/fpsyg.2020.00318
|View full text |Cite
|
Sign up to set email alerts
|

Reformulating and Mirroring in Psychotherapy: A Conversation Analytic Perspective

Abstract: The conversational actions of reformulating and mirroring constitute some of the core intervention techniques of psychotherapy. The purpose of the present study was to investigate the way in which therapists in cognitive-behavioral (CBT) and psychodynamic therapy (PDT) use reformulating and mirroring strategies to return patients' prior talk and how their differential usage can be viewed in light of the respective manualized recommendations. A mixed methods approach was applied using qualitative data that deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
2
12
0
1
Order By: Relevance
“…Some participants referenced the importance of adopting the client's language to support engagement and overcome resistance. This is consistent with conversational analysis studies that have found mirroring of client language can facilitate a shared understanding of client experiences and presenting difficulties (Knol et al, 2020). Furthermore, language style matching by the therapist has been found to increase perceptions of empathy (Lord et al, 2014) and foster development of the therapeutic alliance with clients who may be hypervigilant to rejection (Borelli et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some participants referenced the importance of adopting the client's language to support engagement and overcome resistance. This is consistent with conversational analysis studies that have found mirroring of client language can facilitate a shared understanding of client experiences and presenting difficulties (Knol et al, 2020). Furthermore, language style matching by the therapist has been found to increase perceptions of empathy (Lord et al, 2014) and foster development of the therapeutic alliance with clients who may be hypervigilant to rejection (Borelli et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Practitioners should be mindful that any specific event/experience or explanatory model is likely to be insufficient in explaining the onset of FND, and therefore, the formulation should be held tentatively. Psychological formulations should be paced appropriately as to not overwhelm the client (Dawson & Moghaddam, 2016) with language style matching used to support a shared understanding (Knol et al, 2020). When considering the impact of enacted and internalised stigma, the formulation process may be particularly important in fostering feelings of validation, acceptance, and compassion.…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…This form of repetition serves as an indirect request for elaboration (cf. Knol et al, 2020 ). Instead of further elaboration on the feelings of pity toward her mother, the patient treats the therapist’s other-repeat as a repair initiation and responds by repeating herself (“but also for myself, yes,” line 45).…”
Section: Resultsmentioning
confidence: 99%
“…El Análisis de la Conversación se ha ocupado de describir las funciones discursivas de las repeticiones y las (re) formulaciones dialogales, generalmente por separado, en géneros como la conversación cotidiana (Tannen, 1987;Norrick, 1987;Camacho, 2001;Kim, 2002;Stivers, 2005;Guardiola & Bertrand, 2013;Rossi, 2020, entre otros) e interacciones profesionales como la entrevista terapéutica (Davis, 1986;Antaki, 2003;Antaki et al, 2005;Knol et al, 2020;Yijin, 2021), en las que el hablante recupera el discurso del interlocutor con el propósito de alinearse con él, de ayudarlo a formular su discurso o a construir su historia (Wynn & Wynn, 2006: 1390. En varios de estos últimos estudios los procedimientos de RDI se han analizado con frecuencia en tanto que modos de expresión de empatía con respecto al emisor del turno repetido (Wynn & Wynn, 2006;Knol et al, 2020: 10;Yijin, 2021: 382), entendida esta sobre todo en su dimensión conocida como empatía cognitiva, como la capacidad de reconocer y comprender las emociones de otra persona (Abu-Akel & Shamay-Tsoory, 2013;Cuff et al, 2015;Figueras, 2021: 127 y en prensa).…”
Section: Repeticiones Y (Re)formulaciones Dialógicas En El Análisis D...unclassified